Profile of hospitalizations for schizophrenia, schizotypal and delusional disorders in the municipality of Belém, state of Pará, from 2020 to 2024 (Research, Society and Development, 2025)
Hospitalizations for schizophrenia and schizotypal and delusional disorders showed a continuous increase in the municipality of Belém (PA) between the years 2020 and 2024, reflecting the impact of these severe mental disorders on quality of life. A higher occurrence was observed among young adults, especially in the age groups of 20–29 and 30–39 years, which together accounted for more than half of all hospitalizations during the analyzed period. The study aimed to analyze the annual evolution of these hospitalizations and their characteristics according to sex, race/skin color, and age group. For this purpose, a cross-sectional quantitative epidemiological study was conducted using data extracted from TABNET/DATASUS for the municipality of Belém. Descriptive analyses, comparative graphs, and nonparametric tests (Kruskal–Wallis and Dunn post-hoc) were performed. The results showed a significant increase in hospitalizations, with emphasis on males, who presented a marked discrepancy in 2024, with 1,294 hospitalizations. Additionally, a predominance of individuals self-identified as brown (pardo) was observed across all analyses, confirming the greater representation of this group in the epidemiological profile of hospitalizations. It is concluded that hospitalizations due to psychotic disorders show an upward trend and are mainly concentrated among young adults, reinforcing the need for prevention strategies, early care, and psychosocial rehabilitation, as well as strengthening public mental health policies.